Myeloid and T Cell-Derived TNF Protects against Central Nervous System Tuberculosis - Hsu, Nai-Jen; Francisco, Ngiambudulu M.; Keeton, Roanne; Allie, Nasiema; Quesniaux, Valérie F. J.; Ryffel, Bernhard; Jacobs, Muazzam (Frontiers in Immunology, 2017)
Tuberculosis of the central nervous system (CNS-TB) is a devastating complication of tuberculosis, and tumour necrosis factor (TNF) is crucial for innate immunity and controlling the infection. TNF is produced by many cell types upon activation, in particularly the myeloid and T cells during neuroinflammation. Here we used mice with TNF ablation targeted to myeloid and T cell (MT-TNF-/-) to assess the contribution of myeloid and T cell derived TNF in immune responses during CNS-TB. These mice exhibited impaired innate immunity and high susceptibility to cerebral M. tuberculosis infection, a similar phenotype to complete TNF deficient mice. Further, MT-TNF-/- mice were not able to control T cell responses and cytokine/chemokine production. Thus, our data suggested that collective TNF production by both myeloid and T cells are required to provide overall protective immunity against CNS-TB infection.